1975
DOI: 10.1104/pp.56.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of Ribosomal and Messenger RNAs in Early Wheat Embryo Germination

Abstract: Germinating wheat embryos (Triticum aestivum L). synthesize both ribosomal and messenger RNA at the earliest times after the onset of germination. The rates of synthesis of these two RNAs are determined at various stages in germination by an analysis of newly synthesized radioactive RNA on oligo(dT)-cellulose. The rate of messenger RNA synthesis is essentially constant throughout 18 hours of germination, while that of ribosomal RNA synthesis increases steadily, particularly after the onset of cell expansion (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…in wheat embryos (6). Spiegel et al (18) hr; 11.9 ,ug, 24 hr; 10.7 ,ug. 36 hr; 9.9 ,Lg, 48 hr; 10.5 ,.cg, 60 hr.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…in wheat embryos (6). Spiegel et al (18) hr; 11.9 ,ug, 24 hr; 10.7 ,ug. 36 hr; 9.9 ,Lg, 48 hr; 10.5 ,.cg, 60 hr.…”
Section: Discussionunclassified
“…Investigation of the incorporation of precursors for RNA into acid-insoluble materials in wheat embryos showed that syntheses of mRNA, rRNA, and tRNA were activated and increased as a function of germination periods (6,7,18). Particularly, an experiment using :'2Pi as a precursor indicated that RNA synthesis in wheat embryos up to 24 hr of germination was very low, compared with that between 24 and 48 hr (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that translation of newly synthesized mRNA occurs after a delay of several hours (4,5,7,11 molecules (27). In this material, the initial water uptake is completed after 30 min (19).…”
Section: Introductionmentioning
confidence: 69%
“…Differences In wheat embryos the activities to synthesize mRNA, rRNA, and tRNA were observed to be activated and increased during germination (8,9,11,25,29, 34 (35) reported that the template activity of chromatin with exogenous DNA-dependent RNA polymerase II from wheat embryo was constantly very low for the first 18 h of germination, thereafter increased 2-fold and 5-fold at 24 h and 60 h of germination, respectively, in parallel with the decrease in the amounts of two major nonhistone proteins, mol wt 39k and 59k polypeptides. We have recently demonstrated that some nonhistone proteins, different from 39k and 59k polypeptides, which originated from germ chromatin having very low template activity, inhibited transcriptional activity; whereas those which originated from seedlings having high template activity stimulated transcriptional activity in reconstituted chromatin (36).…”
Section: Introductionmentioning
confidence: 99%